2018
DOI: 10.3201/eid2409.180247
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Endograft Infection with Mycobacterium chimaera and Granulicatella adiacens, Switzerland, 2014

Abstract: We describe an aortic endograft infection caused by Mycobacterium chimaera and Granulicatella adiacens, successfully treated with prolonged antimicrobial drug therapy after complete explantation of the infected endoprosthesis and extra-anatomical reconstruction. Whole-genome sequencing analysis did not indicate a close relationship to bacterial strains known to cause infections after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…AST of environmental M. chimaera isolates recovered from HCUs is important because whole-genome sequencing studies have linked the majority of invasive M. chimaera infections to strains recovered from contaminated HCU devices globally (4). Treatment of invasive M. chimaera infections associated with OHS has been challenging (14,16,17,29). Like other NTM species, M. chimaera appears to be an effective biofilm producer (30).…”
Section: No Of Isolates B With Mics Ofmentioning
confidence: 99%
“…AST of environmental M. chimaera isolates recovered from HCUs is important because whole-genome sequencing studies have linked the majority of invasive M. chimaera infections to strains recovered from contaminated HCU devices globally (4). Treatment of invasive M. chimaera infections associated with OHS has been challenging (14,16,17,29). Like other NTM species, M. chimaera appears to be an effective biofilm producer (30).…”
Section: No Of Isolates B With Mics Ofmentioning
confidence: 99%
“…Mizoguchi et al [13] reported an endovascular device infection with an iliopsoas abscess caused by Mycobacterium tuberculosis var. bovis after intravesical bacillus Calmette-Guérin therapy; Shaikh et al [14] reported an aortic graft infection with a Mycobacterium avium complex in a patient with a human immunode ciency virus infection; and Plate et al [15] reported an aortic endograft infection with Mycobacterium chimaera associated with an outbreak in the high-care units. To the best of our knowledge, this is the rst report of aortic endograft infection with MMA.…”
Section: Discussionmentioning
confidence: 99%
“…Mizoguchi et al [ 13 ] reported an endovascular device infection with an iliopsoas abscess caused by Mycobacterium tuberculosis var. bovis after intravesical bacillus Calmette – Guérin therapy; Shaikh et al [ 14 ] reported an aortic graft infection with a Mycobacterium avium complex in a patient with a human immunodeficiency virus infection; and Plate et al [ 15 ] reported an aortic endograft infection with Mycobacterium chimaera associated with an outbreak in the high-care units. To the best of our knowledge, this is the first report of aortic endograft infection with MMA.…”
Section: Discussionmentioning
confidence: 99%